Characterizing the feeding value of extruded-expelled soybean meal with or without added fat in a commercial swine production facility - M J Webster; J C Woodworth; La Llata M De; N Said; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2000)
A total of 1,200 gilts was used to evaluate the effects of replacing conventionally processed soybean meal with extruded-expelled soybean meal on finishing pig growth performance. Dietary treatments were arranged in a 2 × 3 factorial with two sources of soybean meal (solvent-extracted or extruded-expelled) and three levels of added fat (none, 3.4, and 7% in Phase 1 than decreasing in subsequent phases). Energy levels were adjusted such that the higher energy in extruded-expelled soybean meal (with or without added fat) was equal to that provided by solvent-extracted soybean meal with added fat. From 54 to 135 lb, pigs fed extruded-expelled soybean meal had improved ADG and F/G compared to those fed solvent-extracted soybean meal. Increasing added fat in either extruded-expelled- or solvent-extracted soybean meal-based diets linearly improved ADG and F/G. From 135 to 270 lb, pigs fed extruded-expelled soybean meal and(or) increasing added fat had decreased feed intake. For the overall growing-finishing period, ADG was unaffected by increasing energy density. However, ADFI was decreased and F/G improved as energy density of the diet was increased either with extruded-expelled soybean meal and(or) added fat. Carcass leanness was not affected by dietary treatment. These results indicate that increasing the energy density of the diet by using extruded-expelled soybean meal and(or) added fat improves feed efficiency in finishing pigs reared in a commercial environment.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Soybean meal; Processing; Fat; Growth; Finishing pigs